MEMBANGUN COMMUNITY POLICING MELALUI KEMITRAAN POLISI-KOMUNITAS - Mu'man Nuryana (Politeknik Kesejahteraan Sosial, 2003)
Community Policing Development Through the Collaboration of Police and Community: A Model for Improving Social Resilience in Indonesia.Abstract The idea to changing police paradigm from an emphasis on traditional law enforcement practices toward community-oriented policingan approach that depends on officer-initiated efforts to reduce criminal and public disorder should be launched in Indonesia. Community policing is a philosophy of policing that needs police officers to act with increased levels of autonomy and professional discretion to solve problems and to develop partnerships with the community. This article discussing a conceptual framework of how community policing can be implemented through providing an overview of the context in which community policing has been socialized in the developed countries.Kata Kunci: Community policing, police officer, domestic violence, catalyst, normative sponsorship theory